Grasp synthesis considering graspability for a digital hand with limited thumb range of motion*. (16th February 2022) - Takahashi, Reiko; Miyata, Natsuki; Maeda, Yusuke; Nakanishi, Yuta
Abstract : This paper proposes the synthesis of grasp postures using a digital hand with limited range of motion (ROM) of the thumb. To virtually evaluate universal design products, it is necessary to synthesize natural grasps for different hands, including those with disabilities. In terms of disability, we focused on limited ROM of the thumb, which is typically observed in patients with carpal tunnel syndrome (CTS). Based on a musculoskeletal model, we extended a contact-region-based method for a grasp synthesis to include an ROM-limited hand and succeeded in synthesizing the mechanically feasible grasp postures that viably reflect the grasp features of an ROM-limited thumb. GRAPHICAL ABSTRACT: UF0001